Diseño y construcción de un prototipo automatizado en el area de mezclado y llenado de polipropileno, para la disminución de paros en techoluz de la empresa Tubasec c.a - Medina Yépez, Francisco Javier (2018)
The purpose of this project is to design an automatic mixing system to prevent the operator from trying to load the raw material into the mixer, otherwise problems may arise in the preparation of She product duc to overexertion and generate errors that can cause the sheets don’t fulfill with the parameters of quality, harming the company due to customer dissatisfaction. It is desired to avoid production stoppages by having a complete circuit of level controls in the reception of raw materials, mixing the raw materials according to the required percentage of mixing and dosing without the need of a person in the control of supply of mixture. From the result obtained through surveys to the potential client, the workforce of the Techoluz process, the acceptance of the prototype was achieved since its operation proved its effectiveness, guaranteeing its implementation if required.